2013
DOI: 10.1371/journal.pone.0058703
|View full text |Cite
|
Sign up to set email alerts
|

The p90 Ribosomal S6 Kinase (RSK) Is a Mediator of Smooth Muscle Contractility

Abstract: In the canonical model of smooth muscle (SM) contraction, the contractile force is generated by phosphorylation of the myosin regulatory light chain (RLC20) by the myosin light chain kinase (MLCK). Moreover, phosphorylation of the myosin targeting subunit (MYPT1) of the RLC20 phosphatase (MLCP) by the RhoA-dependent ROCK kinase, inhibits the phosphatase activity and consequently inhibits dephosphorylation of RLC20 with concomitant increase in contractile force, at constant intracellular [Ca2+]. This pathway is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…21, 37 In our current work, we report that β-arrestin signaling increases ERK1/2 phosphorylation as well as RSK3 phosphorylation, signaling to MLC2v. The role of the RSK family members in the development and maintenance of cardiac disease is not understood.…”
Section: Discussionmentioning
confidence: 53%
“…21, 37 In our current work, we report that β-arrestin signaling increases ERK1/2 phosphorylation as well as RSK3 phosphorylation, signaling to MLC2v. The role of the RSK family members in the development and maintenance of cardiac disease is not understood.…”
Section: Discussionmentioning
confidence: 53%
“…Myricetin can be used as a health food on account of its anti-tumor characteristics. Ribosomal S6 kinase (RSK) 2 is a member of the p90RSK protein family, and it can be translocated when activated by neurotransmitters or growth factors [6,7]. Also, RSK2 is involved in many cellular processes, such as proliferation, cell cycle, and apoptosis [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that p90RSK is activated by ERK signal, leading to actin polymerization . It is also demonstrated that activation of p90RSK facilitates SMC contraction . In human aortic smooth muscle, inhibition of MEK/ERK/Elk‐1(ETS transcription factor‐1) and p90RSK pathways reduces both cell proliferation and migration .…”
Section: Discussionmentioning
confidence: 99%